A família da criança vítima de queimaduras: vivência dos pais frente à hospitalização - Viana, Joelma de Matos (2013)
Significant advances in knowledge about burn trauma impacts on the victim and their families have been achieved in recent decades. In order to contribute with these results, this paper aimed to investigate the experience of parents facing the hospitalization and the physical and emotional rehabilitation of child burn victim. Furthermore, as specific goals: Identify how and under what conditions the burns occurred; know the adopted procedure to cope with burn accidents and the feelings experienced due to the process that culminated in the accident and subsequent hospitalization; verify the adoption of preventive measures after the accident. The paper adopted qualitative and interpretative characters following the methodological framework of Grounded Theory. The study was conducted at the Center of Burn Victims Protection, an NGO linked to Burns Hospital in Goiás, with nine mothers and one father who have had their children victimized by burns. Data were collected between June and October 2012 using a semi-structured interview and subsequently analyzed following the initial and focused coding proposed by Charmaz. Four central categories emerged from the analysis, some with subcategories, which are presented as follows: The History of Accident (with the subcategories: Condition and Scene of the Accident and Trauma on the Family); Impacts of the Burn on the Family; Implications of Burn on a Child s Life; course (with the subcategories: Experiences, Coping, Resources and Reinterpretation). The results lead to realize the importance of ensuring the permanence of the family with the child during hospitalization as a key element in the process of recovery of the victim. The painful episodes experienced lead to a reflection and a production of meanings to the illness experience, rearranging the family s life, that learns and reframes their concepts and values from the trauma because it receives unconditional support of professionals during the initial hospitalization and then on the phase of physical and social rehabilitation.